Banking sector governance: Lessons from Hong Kong listed bands. A three year perspective analysis - Sh. D. Chatterjee (The International Journal of Management Science and Information Technology (IJMSIT), 2011)
Hong Kong's financial sector is popular within the banking industry for the range of service providers themselves. Using the case study approach, this paper explores the changes to the boards of directors and governance issues of the 12 listed banks on Hong Kong stock exchange over a three year period. It focuses on issues such as the number of directors on the boards, their qualifications, type of directors in terms of independence, outside directorships held, and the auditors of the financial statements from 2004 to 2006.Through the use of archival data over a three year period, this paper finds that the overall listed banks in Hong Kong exhibit good corporate governance, and that this governance has in fact improved in quality over the years. The three year comparison demonstrates that the high level of corporate governance exhibited by the 12 listed banks in Hong Kong from 2004 to 2006 provides a possible explanation to the success of the region a significant international financial center due to the factors such as absence of duality of CEO and chairman, use of the Big four audit firms, qualifications of directors, and use of independent non-executive directors on the boards. According to Stanwick and Stanwick (2005), the long-term survival of banks is dependent on the success of the boards of directors, as they are the ultimate decision-making bodies of the organizations (Psaros and Seamer, 2002).
Keywords: 650